Implementasi Penilaian Autentik pada Materi Pembelajaran Pendidikan Agama Islam di SDN 329 Suka Damai - Nst, Tini Melinda; Remiswal, Remiswal; Khadijah, Khadijah (Lembaga Yasin AlSys, 2025)
This study originates from the implementation of authentic assessment at SDN 329 Suka Damai, which, although applied in Islamic Education (Pendidikan Agama Islam, PAI) learning, still faces several challenges in practice. Authentic assessment, as a form of evaluation emphasizing the contextual measurement of skills, attitudes, and knowledge, encounters obstacles such as teachers’ difficulties in systematically developing assessment instruments and rubrics, limited time, administrative workload, and a lack of technical training. The aim of this study is to examine how authentic assessment is implemented and to identify the challenges faced by teachers along with the strategies they employ in PAI instruction. The method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The findings show that authentic assessment has been implemented through self-assessment, project-based assessment, and product assessment, but its execution remains suboptimal due to limited technical capacity among teachers and heavy workloads. Strategies used by teachers include adapting assessment instruments from available sources and collaborating with peers in rubric development. In conclusion, continuous training and institutional support from the school are needed for authentic assessment to be implemented more effectively and consistently in PAI learning. The implication is that optimal authentic assessment can foster the holistic development of students’ character and spiritual competencies in alignment with the goals of primary education.